LEGAL SATISFACTION SUSPENDED BY LAND DEED OFFICIAL THAT DOES NOT MEET THE MINIMUM PRICE STANDARD FOR PURCHASING APARTMENT FOR FOREIGNER IN INDONESIA - I Nyoman Sujana; I Nengah Renaya; I Wayan Mustika Adi Prapta (NOTARIIL Jurnal Kenotariatan, 2019)
The aims of this study are to investigate the legal certainty of the Land Deed Official that does not meet the minimum price standard on purchasing apartment units for foreigners domiciled in Indonesia and to examine the consequences of the Land Deed Official that does not meet the minimum price standard on purchasing flats for foreigners. This study is normative legal research that uses a statutory approach and a legal concept analysis approach. Legal materials are collected using the snowball method and analyzed systematically with legal discovery techniques. The results showed that the legal certainty of the Land Deed Official that does not meet the minimum price standard in purchasing flats for foreigners according to the provisions of Article 11 of the Republic of Indonesia Government Regulation Number 103 Year 2015 on Housing Ownership or Occupancy by Foreigners Occupied in Indonesia. the law and the legal consequences of the Land Deed Official which does not meet the minimum price standard for the purchase of flats for foreigners are null and void, because they are contrary to the legal objective conditions of the agreement stipulated in the provisions of Article 1320 of the Civil Code about a particular measure that is clear, required and justified by law.